Cancer history associates with a lower burden of dementia and Alzheimer's‐type neuropathology in autopsied research volunteers. (December 2021) - Karanth, Shama D; McDowell, Jaclyn K; Nelson, Peter T; Katsumata, Yuriko; Kryscio, Richard J; Schmitt, Frederick A; Fardo, David W.; Abner, Erin L
Abstract: Background: Cancer and Alzheimer's disease (AD) are common diseases in aging populations. Intriguingly, prior research has reported a lower incidence of AD among individuals with a history of cancer. The current study was conducted to investigate the association of cancer history with neuropathological and cognitive features. Method: Data were drawn from elderly, longitudinally evaluated participants in a community‐based cohort study of aging and dementia who came to autopsy at the University of Kentucky Alzheimer's Disease Research Center (UK‐ADRC). The UK‐ADRC data were linked to the Kentucky Cancer Registry (KCR), which is a population‐based cancer state surveillance system, to obtain cancer‐related data. We examined the causal relationship between cancer history and neuropathological features and clinical diagnoses using inverse probability weighting to address confounding and selection bias. Linear mixed‐effects models with random intercepts and slopes were used to compare cognitive trajectories in participants with or without cancer history. Result: Included participants (n=785) had a mean [SD] age of death of 83.8 [8.6] years; 60.1% were female (Table 1). History of cancer was reported in 190 (24.2%) participants. The prevalence of ≥1 APOE ε4 allele was lower among the participants with cancer history compared to cancer‐free participants (32.6% vs 42%). Participants with cancer history had significantly lower odds of MCI/dementia at the last UK‐ADRC visit (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.31‐0.65). Participants with cancer history had lower odds of Braak neurofibrillary tangle stages III/IV (OR=0.52 [0.34‐0.79]) and V/VI (OR=0.38 [0.26‐0.55]) vs. 0/I/II. Cancer history was also associated with reduced odds of moderate/frequent neuritic plaques, OR=0.53 (0.37‐0.76); moderate/frequent diffuse plaques, OR=0.53 (0.36‐0.78); and moderate/frequent cerebral amyloid angiopathy, OR=0.58 (0.37‐0.91). TDP‐43, α‐synuclein, and cerebrovascular pathologies were not associated with cancer history. The cancer‐free participants had lower significantly more rapid decline in longitudinally assessed MMSE scores (β= ‐0.47 per year increase in age) than the participants with cancer history (Figure 1). Conclusion: In this study, we showed that cancer history was associated with lower burden of AD pathology and less risk of dementia. These findings provide an additional basis of support for prior epidemiological research reporting a protective association between cancer and AD‐type dementia.